Analysis of water pollution control laws in South Africa : a comparative analysis of South Africa, India and the United Kingdom - Nkosi, Busisiwe Rachel (My University, 2015)
Water is the source of life for human beings, animals and plants also need water for them to grow. The scourge of water pollution in our country due to various reasons is of great concerns and if left unattended will have dire consequences. Uncontrolled water pollution results in health hazards to human beings, animals and other living things. In terms of our Constitution the state as a custodian of all natural resources has a duty to ensure that water as a scarce resource is preserved for the present and future generations. Legislative measures are needed in order to ensure that same prevails. Legislation imposes measure such as a permit and its condition that must be respected by the holder of such permit. Failure to observe the condition of the permit is punishable by law for both corporates and human beings. Most environmental crimes are caused not by a deliberate intention or negligence but by poor or ineffective management systems. Public education is important in ensuring that water pollution does not take place. Authorities must also be strict in ensuring compliance with permits and prevention of water pollution as prevention is better that cure. This dissertation examines water pollution legislation in South Africa, India and the United Kingdom and offers a comparative analysis and recommendations to South Africa. The three countries are developed and also allocated in three different continents. The examination and analysis of how they fight water pollution gives a chance to South Africa on how it may improve its legislation and maintain its water quality.
Thesis (LLM. (Development Management Law)) -- University of Limpopo, 2015
Keywords: Water pollution; 344.46343068; Water -- Pollution -- Law and legislation -- South Africa.